2019
DOI: 10.3390/ijms20143481
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Targeting of KCa Channels to Improve Endothelial Function in the Spontaneously Hypertensive Rat

Abstract: Systemic hypertension is a major risk factor for the development of cardiovascular disease and is often associated with endothelial dysfunction. KCa2.3 and KCa3.1 channels are expressed in the vascular endothelium and contribute to stimulus-evoked vasodilation. We hypothesized that acute treatment with SKA-31, a selective activator of KCa2.x and KCa3.1 channels, would improve endothelium-dependent vasodilation and transiently lower mean arterial pressure (MAP) in male, spontaneously hypertensive rats (SHRs). I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Pre-incubation with SKA-31 (0.1 µM) enhanced the effect of Ach-mediated vasodilation only in sMAs from SHR. In related studies, SKA-31 has been reported to have potentiating effects on Ach-induced EDH-type vasodilation in pressurized sMAs of WKY and SHR [17], murine carotid arteries, dog first-order mesenteric and rat middle cerebral arteries [13,14,19], and in carotid artery hypertensive K Ca 3.1 −/− mice [37]. We hypothesized, that in the presence of a Ca 2+ mobilizing receptor agonists, such as ACh, K Ca channel activator can certainly augment such actions by boosting or “priming” K Ca channel activities, which was previously shown in isolated endothelial cells and intact vascular tissue [38,52].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-incubation with SKA-31 (0.1 µM) enhanced the effect of Ach-mediated vasodilation only in sMAs from SHR. In related studies, SKA-31 has been reported to have potentiating effects on Ach-induced EDH-type vasodilation in pressurized sMAs of WKY and SHR [17], murine carotid arteries, dog first-order mesenteric and rat middle cerebral arteries [13,14,19], and in carotid artery hypertensive K Ca 3.1 −/− mice [37]. We hypothesized, that in the presence of a Ca 2+ mobilizing receptor agonists, such as ACh, K Ca channel activator can certainly augment such actions by boosting or “priming” K Ca channel activities, which was previously shown in isolated endothelial cells and intact vascular tissue [38,52].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it effectively reduces blood pressure in normotensive mice, dogs, and pigs [13,14,15] and in mice with hypertension induced by angiotensin II [13], connexin40 deficiency [16]. SKA-31 is also shown to produce a transient decrease in mean arterial BP that was accompanied by either a reflex tachycardia [14], bradycardia [16] or unchanged heart rate [13,15,17]. Using arterial pressure myography, it has been shown that SKA-31 increased coronary flow in a K Ca 3.1 -dependent manner in diabetic rats [18], evoked concentration-dependent inhibition of myogenic tone in the rat cremaster and middle cerebral arteries [19] and in small mesenteric arteries (sMAs) in a K Ca 2.3 / K Ca 3.1 -dependent manner [20].…”
Section: Introductionmentioning
confidence: 99%